Accelerating progress towards the elimination of mother‐to‐child transmission of HIV: a narrative review. Issue 8 (20th August 2020) - Chi, Benjamin H; Mbori‐Ngacha, Dorothy; Essajee, Shaffiq; Mofenson, Lynne M; Tsiouris, Fatima; Mahy, Mary; Luo, Chewe
Abstract: Introduction: Findings from biomedical, behavioural and implementation studies provide a rich foundation to guide programmatic efforts for the prevention of mother‐to‐child HIV transmission (PMTCT). Methods: We summarized the current evidence base to support policy makers, programme managers, funding agencies and other stakeholders in designing and optimizing PMTCT programmes. We searched the scientific literature for PMTCT interventions in the era of universal antiretroviral therapy for pregnant and breastfeeding women (i.e. 2013 onward). Where evidence was sparse, relevant studies from the general HIV treatment literature or from prior eras of PMTCT programme implementation were also considered. Studies were organized into six categories: HIV prevention services for women, timely access to HIV testing, timely access to ART, programme retention and adherence support, timely engagement in antenatal care and services for infants at highest risk of HIV acquisition. These were mapped to specific missed opportunities identified by the UNAIDS Spectrum model and embedded in UNICEF operational guidance to optimize PMTCT services. Results and discussion: From May to November 2019, we identified numerous promising, evidence‐based strategies that, properly tailored and adopted, could contribute to population reductions in vertical HIV transmission. These spanned the HIV and maternal and child health literature, emphasizing the importance of continued alignment and integration of services. We observed overlap between several intervention domains, suggesting potential for synergies and increased downstream impact. Common themes included integration of facility‐based healthcare; decentralization of health services from facilities to communities; and engagement of partners, peers and lay workers for social support. Approaches to ensure early HIV diagnosis and treatment prior to pregnancy would strengthen care across the maternal lifespan and should be promoted in the context of PMTCT. Conclusions: A wide range of effective strategies exist to improve PMTCT access, uptake and retention. Programmes should carefully consider, prioritize and plan those that are most appropriate for the local setting and best address existing gaps in PMTCT health services.